Applied computational intelligence and soft computing in engineering (Advances in Systems Analysis, Software Engineering, and High Performance Computing (ASASEHPC) Book Series, 2018)
This book provides a discussion forum for adopting the state-of-the-art Computational Intelligence techniques in engineering and technology. This book not only deals with an introduction of the CI techniques along with their several applications but also covers several novel applications of combining CI techniques and utilizing the hybrid forms in different practical areas.